Controlling Ventilation For Safe Escape From Coal Mine Fires (PRIPRINT 93-369) (Society for Mining, Metallurgy & Exploration, 1993)
If a fire occurs outby an underground coal mine section, the immediate safe evacuation of miners from the working section should always be the first action during the rescue operation. Unfortunately, in many cases, the escape-ways (escape routes) dedicated for miners' evacuation are contaminated with fire byproducts from adjacent entries. The purpose of this paper is to present the ventilation control process that will maintain the escape-way free from contaminants and available for travel. Several scenarios in a different section on ventilation system arrangements are analyzed, discussed and presented. To perform these studies, the author used a mine-fire simulator, which provides a dynamic (in real time) representation of the fire's progress and also gives a display, a color-graphic visualization, of the spread of combustion products throughout the ventilation system. Presented and discussed in this paper, also, are ways in which the mine-fire simulator can be used as a training and teaching tool for miners and, particularly, for ventilation and safety personnel.